EFEKTIVITAS TEKNIK HYPNOBIRTHING TERHADAP PENURUNAN TINGKAT KECEMASAN IBU HAMIL PRIMIGRAVIDA DALAM MENGHADAPI PERSALINAN DI KELURAHAN TELUK PURWOKERTO SELATAN - Siti Haniyah (Viva Medika, 2013)
Anxiety in pregnant women is an unpleasant feeling of fear which is accompanied byphysiological symptoms. Increased anxiety is not treated can end in complications ofpregnancy and childbirth. In some developed countries like the United States havedeveloped a non-pharmacological methods to deal with labor that is hypnobirthing.Hypnobirthing is a natural method used to eliminate the fear, panic, tension and otherpressures that haunt the mother during labor. The purpose of this research was todetermine the effectiveness of hypnobirthing techniques to decrease anxiety levelsprimigravida pregnant women in the face of labor in the Gulf Village South Purwokerto.This study is a pre-experimental design with pre-experimental one-group pre-post testdesign using a quantitative approach. The data were obtained using a questionnaire.Samples were 16 pregnant women primigravida. Statistical test using the Wilcoxon SignedRank Test of significance Î± = 0.05. The results showed the average value of therespondents' level of anxiety before hypnobirthing at 27.31 and after 12.12 with thedifference value of 15.188. Statistical analysis showed that hypnobirthing techniques havesignificant effects where p = 0.000 (p <0.05).The conclusion of this study is hypnobirthing technique effectively to decrease anxietylevels of pregnant women in the face of labor in primigravida Gulf Village SouthPurwokerto.Keywords: Hypnobirthing, anxiety, pregnant women primigravida